Supporting Factors For Management Decision Making For The Progress Of Life Insurance Companies - Tanurahardja, Lucy (SEAN Institute, 2024)
Life insurance companies in Indonesia face significant challenges in making management decisions. Technological developments demand major investments in digitalization and data protection, while intense competition from new insurance companies and fintechs forces continuous innovation. All of this requires appropriate and responsive strategies in dealing with complex business dynamics. The research focus aims to identify and analyze supporting factors for management decision making that contribute to the progress of life insurance companies. The research method uses quantitative methods. Information was collected through surveys using questionnaires and literature studies. After the quantitative research data was collected, the data was then analyzed using a regression test tool using the SPSS program. The research found that company culture, communication and expertise have a significant influence as supporting factors in decision making with a significance value of 0.000 < 0.050. This shows that life insurance companies that have strong supporting factors tend to make better management decisions and achieve more rapid progress. This research concludes that supporting factors for management decision making play an important role in the progress of life insurance companies. These supporting factors include company culture, communication and skills that support decision making.